Phenological and life-history responses of a tropical cladoceran Moina micrura to multiple environmental drivers - Razak, Muhammad Raznisyafiq; Aris, Ahmad Zaharin; Mohd Zaki, Muhammad Rozaimi; Md Yusoff, Fatimah; Yusof, Zetty Norhana Balia (CSIRO Publishing, 2024)
Context: Climate change and global warming has led to changes in water-quality parameters, which in turn have negative consequences for zooplankton. Aims: To investigate the effects of various environmental stressors (pH, temperature, photoperiod, and food concentration) on the tropical freshwater microcrustacean Moina micrura. Methods: The study examined the effects of these stressors on survival (lifespan), reproduction (days to first brood, number of broods, and total offspring), growth (individual size and total moulting), physiology (heart rate), and sex-switching effects (total male offspring). Key results: Significant (P < 0.05) reductions in the total offspring, individual size, and heart rate of M. micrura were observed when exposed to acidic (pH 5) and alkaline (pH 9) conditions. Conversely, higher water temperatures (31°C) and longer light exposure (20 h) were found to increase total offspring and heart rate in M. micrura. Furthermore, male offspring were produced only under conditions of food scarcity (no food supply and 1 × 102 cells mL-1). Conclusions: Climate change has a significant effect on the life-history traits of M. micrura, a tropical cladoceran species. Implications: Vital insights that can guide policymakers and practitioners in developing more effective strategies to safeguard and preserve tropical freshwater aquatic habitats, especially those of zooplankton species.